Psychobiological indicators of the subjectively experienced health status - findings from the Women 40+ Healthy Aging Study - Serena Fiacco; Laura Mernone; Ulrike Ehlert (BMC, 2020)
Abstract Background Healthy aging is particularly important in women, as their life-span is generally longer than men's, leaving women at higher risk for age-related diseases. Understanding determinants of women's healthy aging is therefore a major public health interest. Clinical utility of previous research is limited, through its focus on either single psychosocial or biological predictors. The present study investigated psychobiological predictors of women's healthy aging, for the first time including positive psychological traits and biomarkers of healthy aging. Methods Totally, 121 generally healthy women aged 40 to 75 were investigated cross-sectionally. Healthy aging was operationalized via self-rated health (SRH). To gain a nuanced view of the particularities at the upper end of the illness-wellness continuum, women with excellent SRH and those with good SRH were analyzed as distinct groups. Socioeconomic and sociodemographic variables, health behavior, resilience, optimism, and self-worth as well as menopausal symptoms, and levels of steroid hormones and gonadotropins were considered as predictors of SRH. Binary logistic regression analyses using the forward conditional method were performed with the two health status groups as dependent variable. Results Women with a lower body mass index (BMI; OR = .59, 95% CI = .33-1.03), higher intensive physical activity (OR = 2.27, 95% CI = 1.06-4.86), and higher resilience (OR = 2.37, 95% CI = 1.34-4.18) were more likely to rate their health as excellent compared to good. No clinically significant differences could be found regarding endocrine levels. Conclusion Psychobiological indicators (lower BMI, intensive physical activity, higher resilience) discriminated SRH at the top level of the health spectrum. In healthy women, the predictive value of endocrine markers seems to be secondary. Interventions targeting these indicators could promote women's healthy aging.